Study of some Biochemical Parameters in Patients with Coronary Artery Disease with and without Type 2 Diabete - Arif , Muntaha A.; Rasheed , Manal K.; Ismaeel , Ammar A. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Impaired lipid metabolism and vitamin D deficiency are well-recognised risk factors for coronary artery disease (CAD) which is considered the major reason for mortality and morbidity in both high- and low-income countries. The incidence of coronary artery disease is 2-8 folds higher in Type 2 diabetes patients than in those without Type 2 diabetes.Objective: The current study aimed to study some biochemical variables (vitamin D3, lipid profile, insulin, fasting blood glucose, and glycated haemoglobin HbA1c) in patients with diabetes and coronary artery disease and compare them with healthy people.Methods: A case-control study included 190 male subjects divided into four groups: 40 healthy controls, 40 diabetic patients, 55 patients with coronary artery disease, and 55 patients with Type 2 diabetes and coronary artery disease. Were recruited from the catheterization unit in cardiologic clinics of the Iraqi Center for Heart Disease and Specialized Center for Endocrinology and Diabetes, Baghdad Teaching Hospital/ Medical City, during the period from February 2022 to November 2022. Physicians diagnosed them and were evaluated by physical and full medical history. Each group measured all the sample set parameters in the fasting state. The biochemical tests included fasting blood glucose, and lipid profile measured by the colorimetric method, while vitamin D3, insulin, and glycated haemoglobin (HbA1c) were measured by enzyme-linked immunosorbent assay (ELISA). Various statistical analyses were applied to analyse the research data. The statistical analysis was performed using a Student t-test for calculating the probability using the statistical analysis program (PAST version 3.09, 2004). Two-way ANOVA and least significant differences (LSD) post hoc tests were performed, and paired t-tests were done. P < 0.05 was considered statistically significant.Results: About 65.3% of study subjects had Vit.D insufficiency and 16.8% had Vit. D deficiency. A statistically significant difference was found in the mean (± SD) level of BMI, insulin level, vitamin D, HOMA-IR, fasting blood glucose, and HbA1c between the 4 groups. For lipid profile, Control group participants had significantly lower total cholesterol levels in comparison to the other groups. Control group participants had significantly lower triglyceride levels in comparison to the other groups. Control group participants had significantly higher high-density lipoprotein (HDL) in comparison to the coronary artery disease group and coronary artery disease with the Type 2 diabetes group. Control group participants had significantly lower low-density lipoprotein (LDL) in comparison to the coronary artery disease group and coronary artery disease with the Type 2 diabetes group.Conclusions: Depending on the results of the current study, it was found that there is a strong association between low vitamin D and coronary artery disease, and it was found that insulin resistance, which mainly causes type 2 diabetes, has increased health problems in coronary artery disease patients.